المقبولية وعلاقتها بالتوجه نحو العمل التطوعي - محمد، علي عودة; اسكندر، ساجدة مراد (جامعة بغداد - مركز البحوث التربوية والنفسية, 2021)
استهدفت الدراسة الحالية التعرف على المقبولية والتوجه نحو العمل التطوعي لدى موظفي دوائر الدولة والتعرف على طبيعة العلاقة الارتباطية بين المقبولية والتوجه نحو العمل التطوعي لدى موظفي دوائر الدولة، وتحقيقاً لأهداف البحث قام الباحثان ببناء مقياس المقبولية والذي تكون في صيغته النهائية من (٢٨) فقرة، كما قام الباحثان ببناء مقياس التوجه نحو العمل التطوعي والذي تكون في صيغته النهائية من (٢٩) فقرة، وقد استخرجت الخصائص السايكومترية من الصدق والثبات وبطرق مختلفة للمقياسين، ثم قام الباحثان بتطبيق المقياسين على عينة قوامها (٤٠٠) موظف وموظفة وتمت معالجة البيانات باستعمال الوسائل الإحصائية المناسبة وتوصل البحث إلى أن موظفي دوائر الدولة لديهم درجة عالية من المقبولية كما أظهرت النتائج أيضا أن الموظفين لديهم توجه نحو العمل التطوعي بدرجة عالية، وأن هناك علاقة ارتباطية دالة وموجبة بين متغيري المقبولية والتوجه نحو العمل التطوعي. وفي ضوء هذه النتائج قدم الباحثان مجموعة من التوصيات والمقترحات لإجراء بحوث مستقبلية.
The current study aims to identify agreeableness and orientation towards voluntary work of officials in public facilities, as well as to identify the nature of the correlation between agreeableness and orientation towards voluntary work of officials in public facilities. To achieve the aims of the research, the researchers designed the agreeableness scale, which consists of (28) items in its final form. The researchers also built a scale of orientation towards voluntary work, which consists of (29) items in its final form. Psychometric properties of validity and reliability of the two scales were extracted in various ways. The researcher applied the two scales on a sample of (400) officials, the results indicated that the officials in the public facilities have a high degree of agreeableness. The results also showed that the officials have a high level of orientation towards voluntary work. There is a positive significant correlation between agreeableness and the orientation towards voluntary work. In the light of these results, the researchers have offered a set of recommendations and suggestions for future research.
Keywords: علم النفس الاجتماعي -- العمل التطوعي -- المقبولية